Smiles to go - Spinelli, Jerry (New York : Joanna Cotler Books, 2008)
Will Tuppence's life has always been ruled by science and common sense but in ninth grade, shaken up by the discovery that protons decay, he begins to see the entire world differently and gains new perspective on his relationships with his little sister and two closest friends.
Keywords: Brothers and sisters -- Juvenile fiction; Friendship -- Juvenile fiction; Self-actualization (Psychology) -- Juvenile fiction; High schools -- Juvenile fiction